2021
DOI: 10.48550/arxiv.2107.03431
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bayesian model-based clustering for multiple network data

Abstract: There is increasing appetite for analysing multiple network data. This is different to analysing traditional data sets, where now each observation in the data comprises a network. Recent technological advancements have allowed the collection of this type of data in a range of different applications. This has inspired researchers to develop statistical models that most accurately describe the probabilistic mechanism that generates a network population and use this to make inferences about the underlying structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Le et al (2018), Peixoto (2018 and Newman (2018) propose measurement error models which view observed networks as noisy realisations of an unknown ground truth. Along similar lines, Mantziou et al (2021) and Young et al (2022) have recently extended the measurement error models to capture heterogeneity, providing model-based approaches to clustering networks.…”
Section: Related Workmentioning
confidence: 99%
“…Le et al (2018), Peixoto (2018 and Newman (2018) propose measurement error models which view observed networks as noisy realisations of an unknown ground truth. Along similar lines, Mantziou et al (2021) and Young et al (2022) have recently extended the measurement error models to capture heterogeneity, providing model-based approaches to clustering networks.…”
Section: Related Workmentioning
confidence: 99%
“…After this work was completed we learned of very recent related work by Mantziou et al A preprint of their work can be found at [40].…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Other bodies of work have tailored populations of networks, including measurement approaches [4,7,15] and models that generalize the concept of unimodal distributions to networks [11,14]. Several recent contributions have directly addressed the problem of summarizing populations of networks when multiple modal networks are needed [9,17,18,[23][24][25][26][27][28][29]. All these approaches require specifying the number of modes ahead of time.…”
Section: Introductionmentioning
confidence: 99%
“…All these approaches require specifying the number of modes ahead of time. Current solutions to this problem include scree plots [9], regularization with ad hoc priors [18], over-parametrized models [24,25,28], or approximative information criteria [17,23] poorly adapted to network problems. These approaches also demand extensive tuning and significant computational overhead from fitting the model to several choices of the number of modes.…”
Section: Introductionmentioning
confidence: 99%